TOLERANSI KROKOT (Portulaca oleracea L.) PADA NAUNGAN YANG BERBEDA - Melati, Rima; Abdullatif, Zauzah; Rabul, Dilfa (Cannarium, 2020)
AbstractPurslane classified weed as a medicinal plant. Its medicinal properties, so that purslane changes status from wild plants or weeds to cultivation crops. However, to cultivate them, the growth criteria need to be met, such as optimal light intensity and to support purslane growth. The aim of the study is to determine the optimal percentage of light intensity to support growth and purslane yield. The experiments were carried out in the field and several observations were observed in the Laboratory. The method used is a completely randomized design with 4 treatments and 5 repeated. The treatments consist of shade with light intensity of 0%, 25%, 50% and 75%. Analysis to differentiate the treatment using is the smallest significant difference. The results of this study indicate that the shade of 0%, 25%, 50% and 75% affect the diameter of the canopy, fresh weight, specific leaf area, chlorophyll content and the number of stomata. Shade 75% plants produce the best growth in canopy diameter, fresh weight and chlorophyll content. Purslane is more tolerant of environments with limited lightKeywords: Shade, Purslane, Tolerance